2. Identification of Avian Filarial Potential Vectors in Local Chicken (Gallus Domesticus) in Banda Aceh And Aceh Besar - Nur Afriyanti; Yudha Fahrimal; Muhammad Hanafiah; Farida Farida; Rusli Rusli; Arman Sayuti (Jurnal Medika Veterinaria, 2020)
This study aimed at finding out the potential vectors of avian filariasis in four locations where chickens were found infected by avian filaria. The samples used in this study were blood-sucking insect vectors that were caught using a light trap. The four locations were namely Limpok, Lamreung, Tungkop (District of Aceh Besar), and Lampriet (Banda Aceh City). The insects obtained were dissected to find microfilaria in their bodies. The data obtained in this study were analyzed descriptively. The results obtained from the arrests were 141 mosquitoes and a total of 313 gnats. Based on the results of the identification of mosquitoes found in the four dominating locations, namely Culex spp. as much as (72.3%), while the gnat obtained were of the genus Culicodes spp. From the results of the mosquitoes and gnats section, microfilariae were not found. Based on the results of the study it can be concluded that from the four locations only two vectors were found, namely Culex spp. and Culicoides spp.